Hubungan Self-Compassion dengan Self-Objectification pada Mahasiswi Pengguna Tiktok di Kota Jambi - Salsabila Raina Fazra; Rion Nofrianda; Ayu Ulivia; Nurul Hafizah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
This study aims to analyze the relationship between self-compassion and self-objectification among female TikTok users in Jambi City. The study used a quantitative correlational approach with a cross-sectional design. A total of 218 female students in Jambi City aged 18–25 years who actively use TikTok were selected using a purposive sampling technique. The instruments used were the Self-Compassion Scale (SCS) adapted into Indonesian (Skala Welas Diri) and the Objectified Body Consciousness Scale (OBCS). Data analysis used the Pearson Product Moment correlation test. The results showed a significant negative relationship between self-compassion and self-objectification (r = -0.216; p = 0.001). The higher the self-compassion, the lower the tendency for self-objectification. The majority of respondents had moderate to high levels of self-compassion, while self-objectification was in the moderate category. The duration of TikTok use of more than 2 hours per day was associated with a higher tendency for self-objectification. These findings confirm the role of self-compassion as a protective factor against self-objectification in the context of visual-based social media use.